Microstructural Characterization of the Mn Lepidolite Distribution in Dark Red Clay Soils - Simona Elena Avram; Lucian Barbu Tudoran; Gheorghe Borodi; Ioan Petean (Applied Sciences, 2025)
Lepidolite is one of a small number of minerals that contains a significant amount of lithium. Some areas, like the Apuseni and Metalifer Mountains in Romania, present dark red layers intercalated with reddish-yellow clay soils with interesting aspects. X-ray diffraction (XRD) analysis coupled with polarized light optical microscopy (POM) revealed that this dark red soil contains a large amount of fine microstructured lepidolite (24–35%) mixed with quartz sand and fine traces of kaolinite and muscovite. Scanning electron microscopy (SEM) elemental analysis revealed a typical clay composition with Mn traces (specific to red lepidolite), confirming POM observation. SEM also revealed fine tabular platelets of lepidolite with a maximum size of 1.5 µm surrounding quartz particles (5–50 µm), indicating the presence of numerous nano fractions. Their presence was confirmed by atomic force microscopy (AFM), which showed particle sizes ranging from 40 to 60 nm, closely matching the crystallite size estimated using the Scherrer formula. The finest fraction allows easy separation from the quartz sand through bi-distilled water washing. Quartz particles settle at the bottom of the container, while the finest lepidolite particles are easily separated. Water evaporation ensures their recovery. Thus, the enriched lepidolite powder could be utilized for specific applications in the lithium industry. On the other hand, the large number of the finest particles found in the samples investigated presents the risk of PM1, PM2.5m, and PM10 emission, with impacts on atmospheric environmental safety.